Severely curved mandibular molar teeth managed by Nickel titanium K-flex files and balanced force technique (Bangladesh Journal of Dental Research & Education, 2013)
Bangladesh Journal of Dental Research & Education, Vol. 01, No. 01, January 2011, Page 12-14 DOI: http://dx.doi.org/10.3329/bjdre.v1i1.15795